The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/fermentation7030159
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Fatty Acid Production from Organic Waste with the Emphasis on Membrane-Based Recovery

Abstract: In recent years, interest in the biorefinery concept has emerged in the utilization of volatile fatty acids (VFAs) produced by acidogenic fermentation as precursors for various biotechnological processes. This has attracted substantial attention to VFA production from low-cost substrates such as organic waste and membrane based VFA recovery techniques to achieve cost-effective and environmentally friendly processes. However, there are few reviews which emphasize the acidogenic fermentation of organic waste int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 128 publications
(249 reference statements)
0
17
0
Order By: Relevance
“…Undissociated VFA can penetrate cell membrane easily and dissociate within cells' cytoplasm inhibiting growth [31] by disrupting the proton gradient across the cell and blocking ATP synthesis [32]. On the other hand, at higher pH, VFAs can occur in their dissociated form [33,34] leading to an increase in ionic strength at higher concentrations and eventually resulting in cell lysis [23,32]. As minimal or nonsignificant cell toxicity or growth inhibition was observed at 10 mM of each VFA, we opted to use this concentration for each VFA in PHA production in bioreactors from synthetic VFA mix.…”
Section: Discussionmentioning
confidence: 99%
“…Undissociated VFA can penetrate cell membrane easily and dissociate within cells' cytoplasm inhibiting growth [31] by disrupting the proton gradient across the cell and blocking ATP synthesis [32]. On the other hand, at higher pH, VFAs can occur in their dissociated form [33,34] leading to an increase in ionic strength at higher concentrations and eventually resulting in cell lysis [23,32]. As minimal or nonsignificant cell toxicity or growth inhibition was observed at 10 mM of each VFA, we opted to use this concentration for each VFA in PHA production in bioreactors from synthetic VFA mix.…”
Section: Discussionmentioning
confidence: 99%
“…These methods can even provide in situ separation of the VFAs from the fermentation broth and prevent the inhibitory impact of the VFAs on the metabolism of the microorganisms and increase the acid production yield [37]. The performance of various membrane types to recover VFAs has been reviewed [38][39][40]. In general, these techniques are potentially able to enhance the recovery of VFAs.…”
Section: Recovery Of the Vfa From Fermentation Brothmentioning
confidence: 99%
“…The main drawbacks associated with the various membranes are membrane fouling, high energy demand, and not being selective enough toward VFAs in the complex mixture of the fermentation effluent. Furthermore, the high cost of membrane maintenance and replacement hinders the economy of operation [38]. Bóna et al [35] applied nanofiltration (NF), reverse osmosis (RO), forward osmosis (FO), and supported liquid membrane (SILM) to recover VFAs from a model fermentation solution.…”
Section: Recovery Of the Vfa From Fermentation Brothmentioning
confidence: 99%
See 1 more Smart Citation
“…Veeken and Hamelers [12] used Contois kinetics with inhibition of 30 g of volatile fatty acid (VFA) per liter, which yielded an adequate result in treating biowaste. Meanwhile, Veeken et al [13] elucidated the VFA inhibition mechanism by designing a set of experiments for treating organic solid waste. The result showed that no inhibition by non-ionized VFA or VFA can be measured at pH between 5 and 7 and that acidic pH was the inhibitor factor.…”
Section: Introductionmentioning
confidence: 99%